Participatory Communication Patterns on the Rural Agribusiness Development Program In Regency Bogor - Muh. Zainal. S; Djuara P. Lubis; Parlaungan A. Rangkuti (Jurnal Komunikasi Pembangunan, 2014)
Abstract PUAP is a program of business funding provision in the form of a revolving fund for farmers by paying directly into the account of  a Farmers Group Unity (Gapoktan) which is assisted by the extension agent and the supervisor of Mitra Tani. This study resulted in the description of participatory communication pattern, analysis of the relation of members’ individual characteristics, extension agent credibility and Mitra Tani Supervisor to participatory communication pattern in PUAP as well as the analysis of the PUAP success and its relation to participatory communication pattern. The research was carried in the District of Ciampea using correlational descriptive survey method. The total of respondents was 71. Data were analyzed by Spearman's rank test. The results showed that the participatory communication pattern of the extension agent and Mitra Tani Supervisor in PUAP was vertical. It is identified from the one way direction communication, misunderstanding content, and low frequency of communication found in the study. Credibility of extension agent in PUAP was high in the honesty aspect, moderate in expertise (quite expert), but low in attractiveness and familiarity. Credibility of Mitra Tani Supervisor was relatively low. The results of the study suggest that the improvement of communication skills of extension agent and Mitra Tani Supervisor was needed. Besides, the increasing of communication frequency with Gapoktan as well as recepients farmers of PUAP was needed to succeed the program. Keywords:             PUAP, Participatory Communication pattern, Credibility of Extension Agent, Mitra Tani Supervisor.